Household Food Storage in Ancient Israel and Judah - Frank, Tim 1977- (Oxford Archaeopress, 2019)
This volume serves as a source book on domestic food storage in Ancient Israel and Judah by outlining important ethnographic and ancient textual and pictorial sources relevant to the discussion. These allow us to understand the motivated actions in relation to food storage, and the significance of food storage in daily life.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books